Iran : a modern history - Amanat, Abbas (New Haven, CT : Yale University Press, 2017)
Covers the complex history of the diverse societies and economies of Iran against the background of dynastic changes, revolutions, civil wars, foreign occupation, and the rise of the Islamic Republic. Amanat combines chronological and thematic approaches, exploring events with lasting implications for modern Iran and the world. Drawing on diverse historical scholarship and emphasizing the twentieth century, he addresses debates about Iran's culture and politics. Political history is the driving narrative force, given impetus by Amanat's decades of research and study. He layers the book with discussions of literature, music, and the arts; ideology and religion; economy and society; and cultural identity and heritage. --From publisher description.
Part four. A contested revolution and the rise of the Islamic Republic. The making of the Islamic Revolution (1977-1979) -- The guardian jurist and his advocates -- Consolidation of the Islamic Republic (1979-1984) -- Facing the foe: the hostage crisis, the Iraq-Iran War, and the aftermath (1979-1989) -- Society and culture under the Islamic Republic.
Includes bibliographical references (pages 915-944) and index.
Keywords: HISTORY / Middle East / General; HISTORY / Modern / General; HISTORY / Asia / General; HISTORY / Asia; HISTORY / Middle East; HISTORY / Modern; Qajar Dynasty (Iran); 1500-1952; History